(NsLOWARX MORFEM RUSSKOGO QZYKA (B:s (NoKOLO (B52 000 (NSLOW (B/s - (NkUZNECOWA(B, (NaRIADNA iWANOWNAs; (NeFREMOWA(B, (NtATXQNA fEDOROWNAs ((NmOSKWA (B:s (NrUS(B. (NQZ(B.,s, 1986)
(NuKAZ(B.: (NS(B. 823-1121s
Keywords: (NmORFEMA W RUSSKOM QZYKEs; (NrUSSKIJ QZYK (B- (NsLOWARIs